2014
DOI: 10.1002/rcs.1587
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of robot-assisted Ivor-Lewis oesophagectomy with intrathoracic hand-sewn anastomosis in the prone position

Abstract: Our initial results suggest that the reported technique is safe and satisfies the oncological principles. It provides the advantages of minimally invasive surgery by overcoming some limitations of conventional thoracoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…Robot‐assisted TTE in the prone position was reported in two papers as initial series 21, 22. Feasibility and safety of intrathoracic hand‐sewn anastomosis and lymphadenectomy along the recurrent laryngeal nerves during robotic surgery were shown, as early results, in the studies of Cerfolio et al, Trugeda et al, Suda et al, and Kim et al, respectively 23, 24, 25, 26…”
Section: Early Results With Small Series Of Transthoracic Esophagectomymentioning
confidence: 97%
“…Robot‐assisted TTE in the prone position was reported in two papers as initial series 21, 22. Feasibility and safety of intrathoracic hand‐sewn anastomosis and lymphadenectomy along the recurrent laryngeal nerves during robotic surgery were shown, as early results, in the studies of Cerfolio et al, Trugeda et al, Suda et al, and Kim et al, respectively 23, 24, 25, 26…”
Section: Early Results With Small Series Of Transthoracic Esophagectomymentioning
confidence: 97%
“…In RAMIE, the utilization of EndoWrist instruments, the deeper high definition 3D vision, the motion scaling and tremor filtration make a hand-sewn intrathoracic anastomosis possible and easier to accomplish. Trugeda and more recently Bongiolatti (40,41), published personal series of RAILE with hand-sewn intrathoracic esophagogastric anastomosis without increased incidence of leakage, stenosis or prolonged operative time. A published survey by Haverkamp et al (20) shows that nowadays the preferred technique of anastomosis is to stapler the thoracic anastomosis and to hand-sew the cervical ones.…”
Section: Ramiementioning
confidence: 99%
“…It was reported that RA-ILE with double-layer hand-sewn chest anastomosis has a lower complication rate (6.3%) and the absence of anastomotic leakage in a series of 16 patients (14,15). We have started performing RA-ILE with intrathoracic robot-sewn anastomosis recently.…”
Section: Commentsmentioning
confidence: 99%